The National Forgotten League : Entertaining Stories and Observations from Pro Football's First Fifty Years - Daly, Dan (University of Nebraska Press, 2012)
The first fifty years of America's most popular spectator sport have been strangely neglected by historians claiming to tell the "complete story" of pro football. Well, here are the early stories that "complete story" has left out. What about the awful secret carried around by Sid Luckman, the Bears' Hall of Fame quarterback whose father was a mobster and a murderer? Or Steve Hamas, who briefly played in the NFL then turned to boxing and beat Max Schmeling, conqueror of Joe Louis? Or the two one-armed players who suited up for NFL teams in 1945? Or Steelers owner Art Rooney postponing a g.